6a+13+11=0

Simple and best practice solution for 6a+13+11=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a+13+11=0 equation:


Simplifying
6a + 13 + 11 = 0

Reorder the terms:
13 + 11 + 6a = 0

Combine like terms: 13 + 11 = 24
24 + 6a = 0

Solving
24 + 6a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + 6a = 0 + -24

Combine like terms: 24 + -24 = 0
0 + 6a = 0 + -24
6a = 0 + -24

Combine like terms: 0 + -24 = -24
6a = -24

Divide each side by '6'.
a = -4

Simplifying
a = -4

See similar equations:

| 6n+16=26 | | i=1500*.05*3 | | a+-7=8 | | 2(x+6)=10 | | 4x-12=2x+2 | | 6-3x=16+2x | | -8n+10=-7n-6 | | 6k-k=27-4k | | 2x^5-5x^3-12x=0 | | 17x-1=14x-4 | | 5y^2-13y+6=0 | | 4y-2=8y+6 | | y+76=(-93) | | 4x+x=x | | f+19=0 | | k+10=1 | | -7x=-5x-6 | | -4x-8=5y+10 | | 9y-4=6y+2 | | m+5=19 | | -10(x+4)+46=-17-17 | | -5d+3(2d-7)=-5 | | H-6-7h=42 | | c+17=27 | | -5+13=13x-2-12x | | -16r+32=40 | | -0.6x+1.18=-0.4x+8.78 | | 3(5x-1)=16x | | z+9=-10 | | 8y-13y=-24-31 | | x^2=7x-12 | | -9c+2=-43 |

Equations solver categories